β1-syntrophin modulation by miR-222 in mdx mice. - Valeria De Arcangelis; Filippo Serra; Carlo Cogoni; Elisabetta Vivarelli; Lucia Monaco; Fabio Naro (PLoS ONE, 2010)
In mdx mice, the absence of dystrophin leads to the deficiency of other components of the dystrophin-glycoprotein complex (DAPC), making skeletal muscle fibers more susceptible to necrosis. The mechanisms involved in the disappearance of the DAPC are not completely understood. The muscles of mdx mice express normal amounts of mRNA for the DAPC components, thus suggesting post-transcriptional regulation. We investigated the hypothesis that DAPC reduction could be associated with the microRNA system. Among the possible microRNAs (miRs) found to be upregulated in the skeletal muscle tissue of mdx compared to wt mice, we demonstrated that miR-222 specifically binds to the 3'-UTR of β1-syntrophin and participates in the downregulation of β1-syntrophin. In addition, we documented an altered regulation of the 3'-UTR of β1-syntrophin in muscle tissue from dystrophic mice. These results show the importance of the microRNA system in the regulation of DAPC components in dystrophic muscle, and suggest a potential role of miRs in the pathophysiology of dystrophy.